The ameliorative effects of melatonin on acetic acid-induced gastric ulcer in rats via its modulatory effects on gut microbiota - YILDIRIM, ALPER; YEGEN, BERRAK; AKSU, MEHMET BURAK; YÜKSEL, MERAL; ŞİRVANCI, SERAP; ARABACI TAMER, SEVİL (CUKUROVA UNIV, FAC MEDICINE, 2021)
Purpose: The aim of this study was of observe the possible protective effects of melatonin pretreatment on oxidative damage and microbiota alteration due to gastric ulcer in rats. Materials and Methods: Wistar-albino rats were given (n=32) melatonin (4 mg/kg/day), antibiotic mixture (AB; 1g/L ampicillin + 1g/L neomycin + 1g/L metronidazole), melatonin+AB in drinking water for 12 days or tap water for 15 days (control group; n=8). Subsequently, ulcer was induced. All treatments were continued for three days. Gastric tissues were obtained for biochemical and histopathological examinations, and fecal samples from the rectum were stored for bacteriological measurements. Results: MPO and MDA levels were increased in untreated ulcer groups compared to the control group. In addition, the levels of luminol-lucigenin chemiluminescence (CL) and 8-OHdG and TNF-alpha and IL-8 protein expressions were also increased, while TNF-alpha, IL-8, MDA, 8-OHdG, luminol and lucigenin CL levels were significantly decreased in the melatonin-treated ulcer groups. However, melatonin+AB pretreatment increased antioxidant GSH levels and anti-inflammatory IL-10 levels, and suppressed caspase-3 activity and reduced MPO back to control level. Conclusion: We anticipate that melatonin treatment, which is an effective antioxidant and radical scavenger, can accelerate ulcer healing along with antibiotics and increase the variety of bacteria impaired by antibiotics in the colon.
Keywords: Stomach ulcer; acetic acid; melatonin